THE INFLUENCE OF BRAND AWARENESS, PRODUCT QUALITY, AND SERVICE QUALITY ON THE DECISION TO REPEAT ORDER MIE GACOAN AMONG STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, STATE UNIVERSITY OF MAKASSAR - Asriana Yuningsi; Agus Syam; Andi Anggi Kemalasari; Andi Reski Nurhikmah (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of brand awareness, product quality, and service quality on the decision to make a repeat order for Mie Gacoan among students of the Faculty of Economics and Business at Makassar State University. The background of this research is based on the intense competition in the culinary industry, which requires companies to understand the factors that drive customers to make repeated purchases. This research employs a quantitative approach with an explanatory research design and involves 100 respondents selected through purposive sampling. Data were collected using a rating-scale questionnaire and analyzed through multiple linear regression. The findings indicate that brand awareness has a significant yet negative effect on repeat orders, suggesting a mismatch between the brand image perceived by customers and their actual consumption experience. Product quality shows a positive and significant effect, emphasizing that consistency in taste and quality is a key consideration in repeat purchase decisions. Service quality also demonstrates a significant influence through speed, friendliness, and comfort of service. Simultaneously, the three variables significantly affect repeat orders, indicating that actual consumption experience plays a stronger role than brand image in shaping customer loyalty